Using solution-focused brief therapy within an eco-systemic approach to support return to school following an acquired brain injury. Issue 3 (3rd July 2019) - Edmondson, Suzanne; Howe, Julia
ABSTRACT: This paper describes a therapeutic intervention within an eco-systemic approach used to support a pupil's return to school following an acquired brain injury (ABI). The outcomes suggest that there were three key facilitative factors during the reintegration back into school. These were: the psychological formulation of the individual's needs and strengths to support a personalised approach to their reintegration; supporting and educating school staff during the individual's reintegration; and one-to-one therapeutic work with the individual. This paper provides some preliminary support for the use of an eco-systemic model when EPs are undertaking therapeutic work in similar cases. However, as this work is based on a single case study, the findings need to be treated with caution. There is a requirement for further research to provide a more robust evidence base in order to determine the use of therapeutic approaches within an eco-systemic approach.